The study of the ancient literary heritage in the scientific research of Askar Egeubaev (Eurasian Journal of Philology Science and Education, 2025)
After our country gained independence, the national literary studies began to freely and objectively explore and rewrite the historical origins of our native literature. In this context, the scholar and researcher Askar Egeubayev, who devoted his academic and literary efforts to transforming ancient written monuments that describe the history and literary-cultural life of the ancient Turkic peoples into the spiritual heritage of our nation, played a significant role. In this article, we aim to comprehensively examine the multifaceted scientific research, translation efforts, and unique contributions of Doctor of Philology, Professor, Turkologist, literary critic, and translator A.K. Egeubayev. His work focused on the historical-literary artifacts and the study of ancient Turkic heritage. Despite his significant contributions, Askar Egeubayev’s scholarly achievements in literary studies, particularly in connecting the artistic system of Kazakh literature to ancient Turkic heritage and written monuments, have yet to be fully evaluated and recognized at a scientific level. The topical relevance and importance of this research are demonstrated by the need to reevaluate and assess the scholar’s studies with a fresh scientific understanding, as he traced the origins of Kazakh literary studies to the Turkic world and its historical-cultural space. Additionally, the novelty of the article lies in the analysis of Egeubayev's scholarly works aimed at studying ancient Turkic heritage and in identifying his unique contributions to the comprehensive study of literary monuments.Keywords: ancient era literature, ancient Turkic monuments, «Kutadgu Bilig», cultural-historical heritage.